Complete the steps to factor
2 answers:
Answer:
(8x - 1)(7x - 1)
Step-by-step explanation:
Given
56x² - 8x - 7x + 1 ( factor the first/second and third/fourth terms )
= 8x(7x - 1) - 1(7x - 1) ← factor out (7x - 1) from each term
= (7x - 1)(8x - 1)
= (8x - 1)(7x - 1) ← in factored form
Answer:
The answer is 1st point.
Step-by-step explanation:
By following the steps that is shown in the picture :
56x² - 8x - 7x + 1
1.Group pairs of terms with common factor,
(56x² - 8x) + (-7x + 1)
2.Factor the GCF from each group,
8x(7x - 1) - 1(7x - 1)
3.Use distributive property,
(8x - 1)(7x - 1)
You might be interested in
Answer:
25
Step-by-step explanation:
Answer:
Equation ----> 2(c - 40)
c = -40
Step-by-step explanation:
2(c - 40)
= (2c) - (80)
= 2c - 80
= +
c = -40
Ok so the slashes are division so you would divide
The answer should be:
20.875
Hope this helps.
There is no picture given for us to answer the question!